Pengaruh Brand Awareness dan HargaTerhadap Keputusan Pembelian Jasa Kamar di OYO Kota Padang - Wiranto, William Oscar; Abrian, Youmil (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
This research is motivated by the development of the Hospitality business in Indonesia which continues to experience visible growth in recent years, with more and more accommodation service providers emerging, ranging from offers at affordable prices to expensive ones. One of the lodging service providers known to the public as pocket-friendly lodging is OYO Rooms. Some guest reviews via Google reviews contain many problems with price, cleanliness, problems with complete facilities, service and so on. This research aims to conduct an analysis of Brand Awareness and prices at OYO Padang city. In this research, the use of quantitative methods is used. The type of research utilized in research is causal associative or relationships of cause-effect. The data was got through results from survey which were divided into respondents who were the research objects. 58. The Brand Awareness variable average is 3.791 with criteria in Good. The Price variable was gotaverage 3.712 with good criteria in Good. Then the purchasing decision variable was got average is 3.792 with criteria in Good. So, there is an influence in positive and significant of Brand Awareness on the decision to purchase a room at OYO Padang city. There is also an influence between price and the decision to purchase a room at OYO Padang city. The Brand Awareness and Price variables have an influence on the purchasing decision variable, so H1, H2 and H3 are accepted.